Warfarin time in therapeutic range and its impact on healthcare resource utilization and costs among patients with nonvalvular atrial fibrillation. (2nd January 2016) - Deitelzweig, Steve; Evans, Michael; Hillson, Eric; Trocio, Jeffrey; Bruno, Amanda; Tan, Wilson; Lingohr-Smith, Melissa; Singh, Prianka; Lin, Jay
Abstract: Background: Warfarin is efficacious for reducing stroke risk among patients with nonvalvular atrial fibrillation (NVAF). However, the efficacy and safety of warfarin are influenced by its time in therapeutic range (TTR). Objective: To assess differences in healthcare resource utilization and costs among NVAF patients with low (<60%) and high (≥60%) warfarin TTRs in an integrated delivery network (IDN) setting. Methods: Patients with NVAF were identified from an electronic medical record database. Patients were required to have ≥6 international normalized prothrombin time ratio (INR) tests. NVAF patients were grouped into two cohorts: those with warfarin TTR <60% (low TTR) and those with warfarin TTR ≥60% (high TTR). Healthcare resource utilization and costs were evaluated during a 12 month follow-up period. Multivariable regressions were used to assess the impact of different warfarin TTRs on healthcare costs. Results: Among the study population, greater than half (54%, n = 1595) had a low TTR, and 46% ( n = 1356) had a high TTR. Total all-cause healthcare resource utilization was higher among patients in the low TTR cohort vs. the high TTR cohort (number of encounters: 70.2 vs. 56.1, p < 0.001). After adjusting for patient characteristics, total all-cause healthcare costs and stroke-related healthcare costs were 2398 ( p < 0.001) and 687 ( p = 0.02) higher, respectively, for patients in the low TTR cohort vs. the high TTR cohort. Limitations: In this retrospective study, we were only able to evaluate the association and not the causality between healthcare resource utilization and costs with the different warfarin TTRs. Conclusion: Many warfarin-treated NVAF patients have a low warfarin TTR. NVAF patients with low vs. patients with high warfarin TTR used healthcare resources to a greater extent, which was reflected in higher healthcare costs.